PENGARUH STRUKTUR AKTIVA DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - Komariah, Nurul; Nururahmatiah, Nafisah (Balance : Jurnal Akuntansi dan Bisnis, 2020)
This study aims to determine the effect of asset structure and liquidity on capital structure at PT. INDOFOOD SUKSES MAKMUR Tbk. The population in this study is all data from PT. Indofood Sukses Makmur Tbk from the first listing on the Indonesia Stock Exchange in 1994 for 24 years, from 1994 to 2018 with the sample used for 6 years, from 2013 to 2018. The sampling technique used is purposive sampling. Data analysis techniques used are the classical assumption test, multiple linear regression, multiple correlation coefficients, coefficient of determination and hypothesis testing (t-test and f-test). The results of this study prove that the Asset Structure has a partially significant effect on the Capital Structure,because the larger the asset structure, the greater the capital structure, it is due to the existence of a large debt obtained can be large. Liquidity has no significant effect partially on the Capital Structure,where company liquidity does not affect the size of the capital structure, and simultaneously the Asset Structure and Liquidity have significant effect on the Capital Structure at PT. Indofood Sukses Makmur tbk.